REASONS THAT LEAD SKATEBOARDERS TO PRACTICE THE SPORT: A COMPARATIVE STUDY BETWEEN THE STATES OF PARANÁ AND RIO GRANDE DO SUL (Fiep Bulletin - online, 2013)
Adventure sports are expanding in the segments of leisure, education, learning and training; they are practiced each time more by children, adolescents and adults. Skateboarding is one of the sports that is developing, becoming, in Brazil, the second highest in number of practitioners, moving a broad industry of sports equipment in the country. Even when considering the visible growth of the sport, it is noted that there is a great bibliographic and scientific deficiency about the subject, which is considered necessary for the improvement of the athletes' conditions, besides assisting toward the perfect development of the sport. In order for this to happen, it is necessary for the Physical Education Professionals to get acquainted with the modality, valencies, and physical qualities that are worked, difficulties, and even the social factors inserted in its practice. This research compared which motivational factors drive 103 skateboarders, being that 44 are from Rio Grande do Sul and 59 are from Paraná, of both sexes, aged from 12 to 36 years old, to remain in the practice of skateboarding, including psychosocial factors, motors of quality of life and health, and whether there is prejudice concerning the sport. Through the analysis of data it was noted that the pleasure for practicing the sport is the biggest motivational factor for the practitioners in both states, followed by factors of maintaining good health, releasing daily tensions (stress), and also factors involving social conviviality. In regards to prejudice, it is verified that it still occurs, however, in a lower level in the state of Rio Grande do Sul, in comparison to Paraná. It is believed that through a greater understanding about skateboarding, society's views on this modality will change. For this to happen, the development of research and studies related to this sports' modality, is necessary.
Keywords: skateboarding; motivational factors; prejudice